Digital communication strategies of the House of Representatives in the Kingdom of Bahrain and their relationship to enhancing public trust: A field study (The International Journal of Educational Sciences and Arts, 2026)
This study aims to identify and analyze the communication gap between the digital communication strategies adopted by the Bahraini Parliament and their ability to meet the public's informational and interactive expectations. Despite technological advancements and the comprehensive digital transformation, there remains a disparity in the effectiveness of the messages conveyed and their capacity to build bridges of transparency and trust. This necessitates examining the Parliament's communication planning to uncover the nature of the relationship between the Bahraini Parliament's digital communication strategies and the level of public trust within a rapidly evolving digital environment and escalating public expectations. Also, the study aims to assess the current state of the digital communication strategies adopted by the Bahraini Parliament and determine the extent to which these strategies impact digital interactivity and transparency. Furthermore, the study seeks to determine the impact of these digital communication strategies on enhancing public trust through the dimensions of credibility and efficiency. This descriptive study employed a "media survey of the public," considered the most effective methodological tool for monitoring public opinion trends toward legislative institutions. It helps describe the features of the digital communication strategies employed by the Bahraini Parliament from the users' perspective, and then analyzes the impact of these strategies on building trust in the outputs of the digital communication. The methodology also allows for comparisons between different audience segments and the analysis of perceptual differences within the study population and sample. The study population consisted of all Bahraini citizens who follow and use the official digital platforms of the Parliament. The sample was a simple random sample of 400 individuals aged 18 and above, ensuring political awareness among the respondents. The study used a questionnaire as its primary data collection tool.The theory of excellence in public relations was employed to explain the relationship between the digital communication strategies adopted by the Bahraini Parliament and the level of public trust. This theory helped analyze the extent to which the Parliament relies on interactive communication based on dialogue with citizens. The study concludes by presenting a scientific model that explains the nature of the relationship between parliamentary digital communication and public trust. The findings are expected to contribute to bridging a knowledge gap regarding the direction of communication policies for the Bahraini Parliament towards a more efficient and flexible digital environment.
Keywords: Digital Communication Strategies; Bahraini Parliament; Enhancing Trust